2021
DOI: 10.1016/j.jaci.2020.12.635
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of IL-4Rα signaling on B cells limits hyperresponsiveness depending on antigen load

Abstract: Background: B cells play an important role in allergies through secretion of IgE. IL-4 receptor a (IL-4Ra) is key in allergic asthma and regulates type 2 cytokine production, IgE secretion, and airway hyperresponsiveness. IL-4 activation of B cells is essential for class switching and contributes to the induction of B effector 2 (Be2) cells. The role of Be2 cells and signaling via IL-4Ra in B cells is not clearly defined. Objective: We sought to find out whether IL-4Ra-responsive B cells or Be2 function was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(119 reference statements)
1
7
0
Order By: Relevance
“…In vitro studies first showed that Th2 cells (or IL-4) could polarize B cells to produce IL-4, which in turn, amplified Th2 responses ( 5 , 17 ). Subsequently, it was shown that IL-4-responsive B cells are important for Th2 polarization, and promoted clearance of helminthic infections, while worsening asthma and leishmaniasis ( 20 , 21 ). However, the in vivo role of B cell IL-4 per se was unclear, with studies showing that it was required for Th2 responses with resultant worsening of leishmaniasis, but it was not required for Th2 responses and protection from helminthic infections or pulmonary/airway inflammation in allergic asthma ( 7 , 20 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies first showed that Th2 cells (or IL-4) could polarize B cells to produce IL-4, which in turn, amplified Th2 responses ( 5 , 17 ). Subsequently, it was shown that IL-4-responsive B cells are important for Th2 polarization, and promoted clearance of helminthic infections, while worsening asthma and leishmaniasis ( 20 , 21 ). However, the in vivo role of B cell IL-4 per se was unclear, with studies showing that it was required for Th2 responses with resultant worsening of leishmaniasis, but it was not required for Th2 responses and protection from helminthic infections or pulmonary/airway inflammation in allergic asthma ( 7 , 20 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the role of B cell IL-4 in promoting Th2 responses modulating disease in vivo , remains uncertain. Constitutive B cell-specific deletion of IL-4Rα reduced Th2 and increased Th1 responses, enhancing susceptibility to Schistosoma mansoni (controlled by Type 2 responses), while reducing Th2-driven cutaneous Leishmania major infection and house dust mite (HDM)-induced asthma ( 20 , 21 ). These studies establish a clear role for IL-4-responsive B cells in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that IL-4 signaling was indispensable for maintaining Treg cells inhibitory function. Notably, it was Treg cell specific- ( 23 , 26 ), but not systemic ( 27 ) or other types of immune cell specific- IL-4 signaling ( 28 , 29 ) deletion that led to more serious immune inflammatory response, emphasizing the particular promotion by IL-4 signaling on Treg cell immunosuppressive function. The underlying mechanisms causing this discrepancy are worth exploring.…”
Section: The Promotions Of Treg Functions By Effector Th Cell Mechanismsmentioning
confidence: 99%
“…A high dose and a low dose treatment schedule were used to induce symptoms of allergic asthma in mice (31). Mice were anaesthetised with ketamine (Anaket-V;…”
Section: House Dust-mite Induced Allergic Airway Diseasementioning
confidence: 99%